Emergency surgical intervention for bulbar-cervical spinal cord hemorrhage: a case report and review of management strategies - He, Chuan; Zhong, Qi; Yang, Ying; Cao, Gang (Frontiers in Surgery, 2025)
Background and importanceSpinal cord hemorrhage (SCH), particularly involving the bulbar-cervical segment (medulla oblongata to C7), is a rare and life-threatening neurological emergency. Due to its anatomical proximity to respiratory, motor, and sensory centers, it often leads to catastrophic neurological deficits. Etiologies include vascular malformations, coagulopathy, or idiopathic causes, yet its low incidence (<1%) poses significant challenges in early diagnosis and management. Current evidence highlights emergency hematoma evacuation, adequate decompression, and spinal stabilization as critical for improving prognosis, though clinical validation through case-based data remains limited.Case presentationA 28-year-old male presented with acute dyspnea, limb numbness, and progressive weakness (left 1/5, right 2/5 on the Medical Research Council scale) over 2 h. Neurological examination revealed a sensory deficit below the T4 dermatome and bilateral pyramidal signs. Imaging confirmed a hematoma extending from the medulla oblongata to C7, with no evidence of vascular malformations or trauma. Emergency microscopic hematoma evacuation (8 ml) was performed, combined with posterior cervical double-door laminectomy (C3–C7) and pre-contoured rod pedicle screw fixation. Postoperatively, mechanical ventilation was discontinued within 24 h. Sensory levels regressed to T8, and motor function improved progressively (left 3+/5, right 5/5 at 2-month follow-up). Postoperative imaging confirmed complete hematoma resolution and stable instrumentation.ConclusionBulbar-cervical SCH necessitates vigilant monitoring for cardiorespiratory compromise. Multidisciplinary emergency intervention—hematoma evacuation with decompression—effectively halts neurological deterioration. The dual-door laminectomy technique optimizes spinal canal expansion while preserving stability, providing a biomechanical foundation for neural recovery. This case underscores the pivotal role of early surgical decompression and stabilization in achieving favorable long-term outcomes for high-level SCH.